Phenotypic characterization and production performance of local pigs under village settings in the southern highland zone, Tanzania - Mbaga, S.H.; Lymo, C.M.; Kifaro, G.C.; Lekule, F.P. (Cambridge University Press, 2005)
Indigenous pigs in Tanzania are descendants of earlier European introductions. However, a lack of systematic breeding plans, poor husbandry practices, genetic drift and possibly mutation have led to pigs of varied phentypes. A study undertaken in Mbeya region showed that the predominant management system practiced was free ranging and occasionally tethering. The average mature body weights for boars and sows were 57.4 kg and 54 gk, respectively. Coat colour varied, but the predominant colours were white (28%), black and white (24%), and solid black (19.8%). The majority (78%)of pigs had droopy ears and such pigs were found to be significantly (P<0.01) heavier with a longer trunk and increased body length when compared with those with erect ears. Other features include a long and straight face and short curled tail. The overall mean birth weight was 0.9kg while the mean weaning weight was 10.8 kg. The average litter size for local pigs was 6.6 piglets and litter size at weaning was 4.3 piglets. Locally raised pigs served a number of functions including among others, income, provision of meat, cooking fat and manure.